Placental calcium transporter (PMCA3) gene expression predicts intrauterine bone mineral accrual. - Martin, R; Harvey, N; Crozier, SR; Poole, JR; Javaid, M; Dennison, E; Inskip, H; Hanson, M; Godfrey, K; Cooper, C; Lewis, R (2007)
Evidence is accruing that environmental exposures during critical periods of early development induce persisting changes in skeletal growth, and alter fracture risk in later life. We have previously demonstrated that placental calcium transport, partly determined by maternal 25-(OH) vitamin D status, may underlie this phenomenon. However, the precise relationship between expression of calcium transport proteins in the human placenta, and neonatal bone mineral accrual in the offspring, remains unknown. Tissue samples from 70 human placentae were fast frozen in liquid nitrogen and stored at -70 degrees C. A quantitative real time reverse transcriptase polymerase chain reaction was used to measure the mRNA expression of PMCA isoforms 1-4, using beta-actin as a control gene. Neonatal whole body bone area, mineral content and areal density (BA, BMC, BMD) were measured within 2 weeks of birth using DXA. PMCA3 mRNA expression predicted BA (r=0.28, p=0.02), BMC (r=0.25, p=0.04), placental weight (r=0.26, p=0.04) and birth weight (r=0.33, p=0.006) of the neonate. In a multivariate model, the relationship between placental PMCA3 expression and neonatal BMC was independent of maternal height, pre-pregnant fat stores, parity, physical activity, smoking, and calcium intake (p<0.05). Expression of the placental calcium transporter PMCA3 mRNA predicts neonatal whole body bone mineral content. This association may explain, in part, the mechanism whereby a mother's 25(OH)-vitamin D stores influence her offspring's bone mass.